Collaborative Governance in HIV And AIDS Prevention in Sleman District 2018 - Yunita Elianda; Dian Eka Rahmawati (Journal of Government and Civil Society, 2020)
AIDS caused by HIV is a health issue of global concern. In Indonesia, in the first quarter of 2017, the number of HIV cases was 10,376 and AIDS cases were 673. DIY is a tourism city and student city that has a high level of human movement so it is highly likely that behaviors that are at risk of contracting or transmitting HIV and AIDS. DIY has an attraction that makes many people with different socio-economic and demographic backgrounds come to this region. Many tourists from domestic and abroad are interested in the beauty of tourism in DIY. Therefore, collaborative governance among stakeholders is needed in the response to HIV and AIDS. There are eight indicators to see the success of collaborative governance according to DeSeve: Networked Structure, Commitment to a Common Purpose, Trust Among the Participants, Governance, Access to Authority, Distributive Accountability / Responsibility, Information Sharing, Access to Resources. The findings of this study are that cross-sectoral collaboration carried out does not yet have regulations as a guideline in carrying out such collaboration. So that cooperation is only at the stage of mutual involvement in the response to HIV and AIDS, not at the stage of official cooperation that has legality. Because the existence of basic rules is important in collaborative governance as the initial foundation and legitimacy for stakeholders who act. AIDS yang disebabkan oleh HIV adalah masalah kesehatan yang menjadi perhatian global. Di Indonesia, pada kuartal pertama 2017, jumlah kasus HIV mencapai 10.376 dan kasus AIDS sebanyak 673. Daerah Istimewa Yogyakarta (DIY) adalah kota pariwisata dan kota pelajar yang memiliki tingkat pergerakan manusia yang tinggi sehingga sangat mungkin perilaku yang berisiko tertular atau menularkan HIV dan AIDS. DIY memiliki daya tarik yang membuat banyak orang dengan latar belakang sosial ekonomi dan demografi yang berbeda datang ke wilayah ini. Banyak wisatawan dari dalam dan luar negeri tertarik pada keindahan pariwisata di DIY. Oleh karena itu, tata kelola kolaboratif di antara para pemangku kepentingan diperlukan dalam menanggapi HIV dan AIDS. Ada delapan indikator untuk melihat keberhasilan tata kelola kolaboratif menurut DeSeve: Struktur Jaringan, Komitmen untuk Tujuan Bersama, Kepercayaan di antara Para Peserta, Tata Kelola, Akses ke Otoritas, Akuntabilitas / Tanggung Jawab Distributif, Berbagi Informasi, dan Akses ke Sumber Daya. Temuan dari penelitian ini adalah bahwa kolaborasi lintas sektoral yang dilakukan belum memiliki peraturan sebagai pedoman dalam melakukan kolaborasi tersebut sehingga kerja sama hanya pada tahap keterlibatan timbal balik dalam penanggulangan HIV dan AIDS, bukan pada tahap kerja sama resmi yang memiliki legalitas. Bagaimanapun juga, keberadaan aturan dasar menjadi penting dalam tata kelola kolaboratif sebagai landasan awal dan legitimasi bagi para pemangku kepentingan yang bertindak.